My face to the wind : the diary of Sarah Jane Price, a prairie teacher - Murphy, Jim, 1947- (Dear America, 2001)
Following her father's death from a disease that swept through her Nebraska town in 1881, teenaged Sarah Jane must find work to support herself and records in her diary her experiences as a young school teacher.